Content integrity and non‐repudiation preserving audio‐hiding scheme based on robust digital signature. Issue 11 (12th February 2013) - Zhu, Liehuang; Liu, Dan; Yu, Litao; Xie, Yuzhou; Wang, Mingzhong
ABSTRACT: Current secure communication schemes do not take together traffic security and data security (content integrity and non‐repudiation) of the secret message into consideration, making the content prone to blind tampering and compromised party cheating attacks. In this paper, we present a scheme that hides secret audio in cover audio on the basis of robust digital signature to preserve not only hidden communication but also content integrity and non‐repudiation of the secret audio. Furthermore, instead of traditional binary authentication that only outputs yes or no, the authentication of our scheme is flexibly measurable, and the measurement value is in correspondence with the sense of human hearing precisely. Experimental results show that the proposed scheme provides highly robust authentication against content‐preserving degradations with 99.03% of test audios having the strongest authenticity (1.00) and high level of distinct authentication between content‐destructive degradations with 95.01% of test audios having relatively weak authenticity (less than 0.15). As the authentication is flexibly measureable, there is no false alarm in the semantic aspect. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This paper presents a scheme that hides secret audio in cover audio on the basis of robust digital signature to preserve not only hidden communication but also content integrity and non‐repudiation of the secret audio. Authentication of the scheme is flexibly measurable, and the measurement value is in correspondence with the sense of human hearing precisely. Experimental results show that the proposed scheme provides highly robust authentication against content‐preserving degradations and high level of distinct authentication between content‐destructive degradations.